Stress, the Autonomic Nervous System, and the Immune-kynurenine Pathway in the Etiology of Depression - Won, Eunsoo; Kim, Yong-Ku (Current Neuropharmacology, 2016)
The autonomic nervous system is one of the major neural pathways activated by stress. In situations that are often associated with chronic stress, such as major depressive disorder, the sympathetic nervous system can be continuously activated without the normal counteraction of the parasympathetic nervous system. As a result, the immune system can be activated with increased levels of proinflammatory cytokines. These inflammatory conditions have been repeatedly observed in depression. In the search for the mechanism by which the immune system might contribute to depression, the enhanced activity of indoleamine 2,3- dioxygenase by pro-inflammatory cytokines has been suggested to play an important role. Indoleamine 2,3-dioxygenase is the first enzyme in the kynurenine pathway that converts tryptophan to kynurenine. Elevated activity of this enzyme can cause imbalances in downstream kynurenine metabolites. This imbalance can induce neurotoxic changes in the brain and create a vulnerable glial-neuronal network, which may render the brain susceptible to depression. This review focuses on the interaction between stress, the autonomic nervous system and the immune system which can cause imbalances in the kynurenine pathway, which may ultimately lead to major depressive disorder.
Keywords: immune system